PET imaging of ischaemic myocardial injury and angiogenesis - Grönman, Maria (fi=Turun yliopisto|en=University of Turku|, 2020)
The myocardium of patients with coronary artery disease (CAD) often is a mixture of ischaemic but viable tissue and irreversibly injured scar tissue. The viable tissue has capability of functional recovery after restoration of blood flow and the assessment of myocardial viability is important in identifying patients who will most likely benefit from revascularisation. Angiogenesis is an essential part of the healing process after ischaemic myocardial injury aiming at restoration of intact tissue capillary network. Measurement of myocardial blood flow by positron emission tomography (PET) and [15O]water is widely used in the evaluation of CAD, but its value in the assessment of myocardial viability is incompletely understood. [68Ga]NODAGA-RGD is a novel PET tracer binding to αvβ3 integrin that plays a central role in angiogenesis and therefore, may enable imaging of angiogenic activity. The purpose of this thesis was to evaluate [15O]water and [68Ga]NODAGA-RGD for the assessment of myocardial viability and ischaemic myocardial injury by PET in experimental models. We used pig models of surgically or percutaneously induced coronary stenosis and human cell based in vitro model of angiogenesis. In the first substudy, we found that resting myocardial blood flow (MBF), perfusable tissue fraction (PTF) and perfusable tissue index (PTI) by [15O]water PET detected myocardial viability with good accuracy in pig models of ischaemic heart failure and myocardial ischaemia. In the second substudy, we found that [68Ga]NODAGA-RGD demonstrated increased myocardial αvβ3 integrin expression in the ischaemic myocardium that was localised in the irreversibly injured myocardium. In the third substudy, we found that the uptake of [68Ga]NODAGA-RGD was proportional to angiogenic activity in an in vitro angiogenesis tissue model. In conclusion, these experimental studies indicate that resting MBF, PTF and PTI by [15O]water PET are useful indexes of myocardial viability in chronic CAD. [68Ga]NODAGA-RGD PET may be useful for the identification of αvβ3 integrin activation associated with recent ischaemic myocardial injury. This tracer reflects angiogenetic activity in vitro, but its specificity for angiogenesis in vivo remains uncertain.

Sydänlihaksen iskeemisen vaurion ja uudisverisuonituksen PET kuvantaminen Sepelvaltimotautipotilaiden sydänlihas koostuu usein iskeemisestä, mutta elinkykyisestä ja peruuttamattomasti vaurioituneesta kudoksesta. Elinkykyisen sydänlihaksen toiminta voi palautua normaaliksi verenkierron palauttamisen jälkeen, ja elinkykyisyyden arviointi on tärkeää verenkierron palauttamisesta hyötyvien potilaiden tunnistamisessa. Uudisverisuonitus eli angiogeneesi, jonka tarkoitus on palauttaa kudokseen toimiva hiussuoniverkosto, on tärkeä osa iskeemisen vaurion jälkeistä paranemista. Sydänlihaksen verenvirtauksen mittaaminen positroniemissiotomografialla (PET) käyttäen merkkiaineena [15O]vettä on paljon käytetty menetelmä sydäntaudin arvioinnissa, mutta sen soveltuvuutta sydänlihaksen elinkykyisyyden arviointiin ei tiedetä. [68Ga]NODAGA-RGD on uusi angiogeneesiä säätelevään αvβ3 integriiniin sitoutuva merkkiaine jonka avulla voitaisi mahdollisesti kuvantaa sydänlihaksen angiogeenistä aktiivisuutta. Väitöskirjatyön tarkoituksena oli arvioida [15O]vesi ja [68Ga]NODAGA-RGD PET:n käyttökelpoisuutta sydänlihaksen elinkykyisyyden ja iskeemisen sydänlihasvaurion tunnistamisessa kokeellisilla malleilla. Käytimme sikoja, joille oli aiheutettu sepelvaltimotukos kirurgisesti tai katetrisaatiolla, sekä ihmissolupohjaista kokeellista angiogeneesin kudosmallia. Ensimmäisessä osatyössä havaitsimme, että [15O]vesi PET:n tehokkuus elinkykyisyyden havaitsemisessa iskeemisen sydämen vajaatoiminnan ja sydänlihasiskemian sikamalleissa oli hyvä. Toisessa osatyössä havaitsimme, että [68Ga]NODAGA-RGD:llä voitiin havaita lisääntynyt αvβ3 integriiniaktivaatio, joka sijaitsi peruuttamattomasti vaurioituneessa sydänlihaksessa. Kolmannessa osatyössä havaitsimme, että [68Ga]NODAGA-RGD:n kertymä oli verrannollinen angiogeneesiaktivaatioon kokeellisessa angiogeneesin kudomallissa. Yhteenvetona voidaan todeta, että [15O]vesi PET on käyttökelpoinen sydänlihaksen elinkykyisyyden arvioinnissa kroonisessa sepelvaltimotaudissa. [68Ga]NODAGA-RGD PET voi olla käyttökelpoinen tuoreeseen sydänlihasvaurioon liittyvän αvβ3 integriiniaktivaation kuvantamisessa. Tämä merkkiaine kuvastaa angiogeenistä aktivaatiota kokeellisesti, mutta sen tarkkuus elävässä elimistössä on epäselvää.